278 REAL WORLD VALIDITY OF THE VARIABLE INDICATIVE OF PLACEMENT SCORE. (25th October 2022) - Ward, L; Garvey, N; Laguna, R; Pender, C; Magner, S; Binions, L; Carrabine, N; Ramiah, V; Byrne, C
Abstract: Background: The Clinical Frailty Scale (CFS) is a widely used frailty measurement that is recommended for use as part of a Comprehensive Geriatric Assessment. The Variable Indicative of Placement (VIP) score was developed to identify at triage in the emergency department patients who require geriatric input. There have only been a limited number of previous studies that have validated the VIP score for use at triage. Current practice in our hospital is to use the VIP score at triage to identify frail older patients and to use the CGA as part of the CGA performed by the Frailty Intervention Team (FIT). We aimed to assess the validity of the VIP tool to identify frail, older patients as identified using the CFS. Methods: A retrospective analysis was performed using routine data collected for the month of November 2021. Inclusion criteria were patients over the age of 65 who had both a VIP and CFS performed. We used a CFS of 1-4 to define fit patients and 5-9 to define frail patients. Similarly for the VIP score we defined fit as VIP negative and frail as VIP positive. Statistical analysis was performed using Microsoft Excel. Results: 267 patients were identified as meeting the inclusion criteria. 157 patients were found to be positive for frailty using the VIP score and 123 using the CFS. The sensitivity of the VIP score was 75% and the specificity was 55%. The positive predicative value was 59% and negative predictive value was 72%. Conclusion: The VIP score fails to perform well in the real world as a screening tool for frailty in comparison to the CFS.